Analgesic and Anti-Arthritic Activities of Polysaccharides in Chaenomeles speciosa - Huang, Doudou; Jiang, Shenggui; Du, Zenan; Chen, Yanhong; Xue, Dan; Wang, Xiujuan; Li, Mengshuang; Zhang, Feng; Chen, Wansheng; Sun, Lianna (Frontiers in Pharmacology, 2022)
Chaenomeles speciosa (Sweet) Nakai has been long used as a folk medicine for rheumatic diseases treatment. This study aimed to investigate the effects and underlying mechanism of polysaccharides in Chaenomeles speciosa (CSP) on the pro-inflammatory cytokines and MAPK pathway in Complete Freund's adjuvant (CFA)-induced arthritis and LPS-induced NR8383 cells. We used acetic acid (HAc)-induced writhing and CFA induced paw edema to determine the analgesic activity and anti-inflammatory activity, respectively. CFA rats were administered CSP (12.5, 25.0 and 50.0 mg/kg) daily for 3 weeks via oral gavage. The analgesic test was done using three different doses of the extract (50 mg/kg, 100 mg/kg, and 200 mg/kg). The anti-arthritic evaluation involved testing for paw swelling, swelling inhibition, and histological analysis in CFA rats. Finally, ELISA, western blot, qRT-PCR were done to determine the effect of CSP on the activation of MAPK pathway, production of pro-inflammatory cytokines in lipopolysaccharide (LPS)-stimulated NR838 macrophage cells. In pain models, oral uptake of CSP greatly reduced pain perception. Furthermore, in CFA rats, CSP substantially decreased paw swelling as well as synovial tissue proliferation and inflammatory cell infiltration. In addition, CSP was shown to inhibit pro-inflammatory cytokines (TNF-a, IL-1β, and COX-2) as well as JNK and ERK1/2 phosphorylation in LPS-stimulated NR8383 cells. Thus, pro-inflammatory cytokine secretion and MAPK signaling downregulation promoted the analgesic and anti-arthritic effects of CSP.